2021
DOI: 10.3390/polym13223980
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Thermal Degradation of Disinfected COVID-19 Non-Woven Polypropylene—Based Isolation Gown Wastes into Carbonaceous Char

Abstract: Yields of carbonaceous char with a high surface area were enhanced by decreasing the temperature to improve the conversion of hazardous plastic polypropylene (PP), the major component in abundantly used isolation gowns. This study applied pyrolysis with different low pyrolytic temperatures to convert disinfected PP-based isolation gown waste (PP-IG) into an optimised amount of char yields. A batch reactor with a horizontal furnace was used to mediate the thermal decomposition of PP-IG. Enhanced surface area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The photographs of the HAC‐OG residues are given in Figure S2. From the SEM image of the residues shown in Figure 7c, one can observe that the surface of the co‐gasification‐based residue is rough due to the depolymerized structures 35 . In Figure S2b, these structures are clearly visible at higher magnification (5KX).…”
Section: Resultsmentioning
confidence: 94%
“…The photographs of the HAC‐OG residues are given in Figure S2. From the SEM image of the residues shown in Figure 7c, one can observe that the surface of the co‐gasification‐based residue is rough due to the depolymerized structures 35 . In Figure S2b, these structures are clearly visible at higher magnification (5KX).…”
Section: Resultsmentioning
confidence: 94%
“…Much research showed that the temperature range for SARS-CoV-2 disinfection is the same as that suggested for TCR reactions for water purification. Researchers pursuing thermal inactivation to combat SARS-CoV-2 are in the early stages of this research ( Harussani et al 2021 ). Under various environmental conditions, the TCI of a surrogate for human norovirus, a virus, takes 40 days to remain on diaper or feces for viral survival.…”
Section: Renewable Energymentioning
confidence: 99%
“…Natural fibers are environmentally beneficial, costeffective, recyclable, densely low and nonabrasive as well as important to reduce the dependent towards plastics. [20,21] In addition, green and renewable products have great potential to dominate the structural, automotive and furniture sectors as it promotes zero carbon footprint and eco-friendly. [3,22,23] Due to its superior mechanical and thermal qualities, as well as its contribution to environmental sustainability, sugar palm fiber (SPF) derived from the sugar palm tree (Arenga pinnata) has been widely regarded as a crucial source of fiber for reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers are environmentally beneficial, cost‐effective, recyclable, densely low and nonabrasive as well as important to reduce the dependent towards plastics. [ 20,21 ] In addition, green and renewable products have great potential to dominate the structural, automotive and furniture sectors as it promotes zero carbon footprint and eco‐friendly. [ 3,22,23 ]…”
Section: Introductionmentioning
confidence: 99%